Gum Arabic as a Cause of Occupational Allergy. (19th May 2011) - Viinanen, Arja; Salokannel, Maija; Lammintausta, Kaija
Abstract : Background . Gum arabic is a potential sensitizer in food industry. Methods . We examined 11 candy factory workers referred to examinations due to respiratory and skin symptoms paying attention to exposure and sensitization to gum arabic. Skin tests, pulmonary function tests, and respiratory provocation tests were carried out as indicated by the symptoms and findings. Results . Occupational asthma, caused by gum arabic was diagnosed in 4/11 candy factory workers and two of them had also occupational contact urticaria and one had occupational rhinitis. One of them had oral symptoms associated with ingestion of products containing gum arabic. Conclusions . Airborne exposure to gum arabic may cause sensitization leading to allergic rhinitis, asthma, and urticaria.